(untitled) (Conference Series, 2022)
Tough times are a real test and a maker of great leaders. Those who emerge as great leaders are those who have a proper strategy in place for allocating scarce resources. The crisis for Christian leaders, especially church leaders in Indonesia, is the lack of ability to face adversity through the right strategy. The root of this problem is the dichotomous mindset of church leaders that separates biblical knowledge from strategic knowledge. Ironically, the Bible has all knowledge of strategy. Furthermore, it should be the basis for determining the right strategy. In constructing a strategy, leaders should collect data through surveys and observation, provide clear and concise directions, and involve the right people in their teams. They should also consider where the younger generations fit into this process. When implementing a strategy, leaders should focus on making progress through concrete steps rather than just holding events, and prioritize urgent tasks while also keeping the overall vision and spirit of the organization in mind.